Improving Color and Shape-Based Classification Skills through Logical Block Play in Group B Kindergarten Children - Siska Listya Purwanti (Madiha Press, 2026)
Classification skills based on color and shape are fundamental cognitive abilities that are important to develop in early childhood, as they play a crucial role in training logical thinking, observation, and the ability to distinguish object characteristics. This study aims to improve color and shape-based classification skills in Group B kindergarten children through the implementation of logical block play. The study utilizes the Classroom Action Research (CAR) method conducted in two cycles, with 20 Group B kindergarten children as the research subjects. Data collection techniques included observation, documentation, and children's performance assessment. The results showed an increase in children's classification abilities in each cycle. In Cycle I, the completeness of color classification reached 55% and shape classification was 50%. After instructional improvements were made in Cycle II, completeness increased to 85% for color classification and 80% for shape classification. The research findings indicate that the structured, gradual, and engaging implementation of logical block play is effective in improving the color and shape classification skills of Group B kindergarten children.